Continuous ST‐Monitoring Function of Implantable Cardioverter Defibrillator Detects Silent Ischemia in Patients With Coronary Artery Disease. Issue 13 (3rd July 2018) - Watanabe, Tetsuya; Hirooka, Keiji; Furukawa, Yoshio; Yabuki, Masanori; Hirata, Akio; Kashiwase, Kazunori; Shutta, Ryu; Mine, Takanao; Mizuno, Hiroya; Tanaka, Toshikazu; Doi, Takahiro; Yoshida, Akihiro; et al.
Abstract : Background: Newer implantable cardioverter defibrillators can monitor intracardiac ECGs, but their ability to detect ischemia is unclear. This study investigated the usefulness of implantable cardioverter defibrillators with an ST‐monitoring function in coronary artery disease patients. Methods and Results: We conducted a prospective study of implantable cardioverter defibrillator patients with the ST‐monitoring function. One hundred seventy‐three patients who received implantable cardioverter defibrillators for primary or secondary prevention of sudden cardiac death. All patients underwent medical examinations at least every 6 months, with standard 12‐lead ECGs and device checks that included analysis of the ST‐monitoring function. Myocardial perfusion imaging or coronary angiography was performed during the follow‐up. The mean follow‐up duration was 23.3±7.7 months. Significant ST changes occurred in 15 patients (8.7%), of whom 14 were asymptomatic. The incidence of angina pectoris was significantly higher in the ST change (+) group than that in the ST change (−) group (28.6% versus 7.2%, P =0.03). In the patients who underwent myocardial perfusion imaging, the sensitivity, specificity, and negative predictive value of the ST‐monitoring feature to detect ischemia were 75.0%, 72.5%, and 93.5%, respectively. The sensitivity, specificity, and negative predictive value of the ST‐monitoring feature to predict residual stenosis evaluated using coronary angiography were 76.9%, 83.5%, and 97.5%, respectively. The percentage of patients with a septal right ventricular lead was significantly lower in the ST change (+) group than in the ST change (−) group (13.5% versus 33.5%, P =0.01). Conclusions: If intracardiac ECGs ST changes are detected, it is necessary to use additional modalities even in asymptomatic patients. Clinical Trial Registration: URL: upload.umin.ac.jp . Unique identifier: UMIN000011824.